Studi Komparatif Pemanfaatan Skripsi Cetak dan Skripsi Non Cetak di UPT Perpustakaan UIN Datokarama Palu Sebagai Sumber Referensi: Analisis Preferensi dan Kepuasan Mahasiswa - Timbang, Sahrul Sidiq; Muliyadi, Irvan; Mathar, M. Quraisy (Literatify: Trends in Library Developments, 2026)
This research discusses the utilization of printed theses and digital theses at the UPT Library of UIN Datokarama Palu as reference sources for students. This research uses a quantitative descriptive approach with a comparative method. The research population is the final semester students of UIN Datokarama Palu, with a sample size of 99 respondents selected using incidental sampling technique. The data collection methods used are observation and questionnaire. The data analysis conducted in this research is using the assistance of the (SPSS) version 25 to carry out data analysis activities. The research results show that the average utilization rate of digital theses is 3.08, while printed theses achieve an average of 2.99, both falling within the good category. Based on the results of the Paired Sample t-Test, a significance value of 0.062 was obtained with a calculated t-value of -1.886. This significance value is greater than the significance level of 0.05, and the calculated t-value is smaller than the table t-value, which means there is no significant difference between the utilization of printed theses and digital theses as student reference sources.